Qing-Yi Decoction in the Treatment of Acute Pancreatitis: An Integrated Approach Based on Chemical Profile, Network Pharmacology, Molecular Docking and Experimental Evaluation - Wei, Tian-Fu; Zhao, Liang; Huang, Peng; Hu, Feng-Lin; Jiao, Ju-Ying; Xiang, Kai-Lai; Wang, Zhi-Zhou; Qu, Jia-Lin; Shang, Dong (Frontiers in Pharmacology, 2021)
Background: Qing-Yi Decoction (QYD) is a classic precompounded prescription, and it has satisfactory clinical effect on Acute pancreatitis (AP). However, the effective constituents and molecular mechanism of QYD in treating AP have not been clarified. Methods: In the present study, a rapid, simple, sensitive and reliable ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS)-based chemical profiling was firstly established in order to identify active constituents in QYD. A network pharmacology analysis was further performed to elucidate the potential targets and signal pathways involved in the treatment of QYD on AP. Finally, the prediction results of network pharmacology were verified through molecular docking and western blot assays. Results: A total of 110 compounds containing flavonoids, phenolic acids, alkaloids, monoterpenes, iridoids, triterpenes, phenylethanoid glycosides, anthraquinones and other miscellaneous compounds were identified, respectively. 11 important components, 47 key targets and 15 related pathways based on network pharmacology analysis were obtained. Molecular docking simulation indicated that ERK1/2, c-Fos and p65 may play an important role in QYD against AP. Finally, the western blot experiments showed that QYD can up-regulate the expression level of ERK1/2 and c-Fos, while down-regulate the expression level of p65. Conclusion: This study predicted and validated the related mechanism of QYD in treating AP and provide directions for further experimental studies.